Potential Energy Savings for Three Daily Load Profiles Through Reduced Distribution Transformer Losses - Ferreyra, Diego M.; Szwarc, Gerardo D.; Sarmiento, Ana C. (IEEE, Institute of Electrical and Electronics Engineers, 2025)
In this work, daily energy losses were calculated for a 13,2/0,4 kV/kV, Dy11, 50 Hz, 100-kVA distribution transformer using three different load profiles based on real measurements. One of the profiles was also applied to a 400-kVA transformer. The calculations were performed for a traditional transformer as per Argentinian standard IRAM 2250 and for two high-efficiency versions, their losses being proposed based on feasible literature alternatives. High efficiency version 1 for each transformer features lower no-load losses and the same total losses; in version 2, both no-load and load losses are reduced. The apparent and active power measurements were made on a university campus with a focus on evening classes; on a company with mixed manufacturing and commercial activities; and on a continuous operation manufacturing plant. The results provide a hint as to the actual savings on transformer energy losses for such realistic daily load profiles, which is key to orient further studies regarding the incorporation of high-efficiency distribution transformers in the Argentinian market.
Keywords: Distribution transformers; Load losses; No-load losses; High efficiency; Daily load profile